Trade Performance Of Fishery Industry In Malaysia - Soh, Bee Hui (2023)
Although Malaysia is a small open economy surrounded by ocean, it still faces critical fish trade deficit, implying that Malaysian fishery industry might lose its export advantage and trade competitiveness globally. This issue has drawn greater attention of policymakers as it poses threats to the Malaysian economic stability, food security and trade performance. The general objective of this study is to evaluate the trade performance of fishery industry in Malaysia, and is divided into five specific ones. First, to measure Malaysian fish export advantage through Revealed Comparative Advantage, Revealed Symmetric Comparative Advantage, Normalized Revealed Comparative Advantage and Comparative Export Performance (CEP). Second, to examine factors (i.e., fish consumption and fish production) affecting CEP for 2001-2020, adopting the Autoregressive Distributed Lag (ARDL) approach. Third, to measure Malaysian fish trade competitiveness through Relative Trade Advantage, Revealed Competitiveness, Trade Competitiveness, Export-Import Ratio and Trade Coverage (FTB). Fourth, to investigate factors (i.e., trade openness, the exchange rate, fishery employment, and foreign income) affecting FTB in 1976-2018, using the Nonlinear Autoregressive Distributed Lag (NARDL) approach. Fifth, to measure the competitiveness of Malaysian fish exports to the prime neighbouring destinations through the Constant Market Share Competitiveness (CMSC) and Constant Market Share Space (CMSS).